The programme of the Swedish Social Democratic Labour Party : adopted by decision of the Party at its seventeenth Congress, 1944. (Stockholm : Sveriges Socialdemokratiska Arbetareparti, 1944)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: arbeiderspartij; Zweden